GreenGate 2.0: backwards compatible addons for assembly of complex transcriptional units and their stacking with GreenGate - Piepers, Marcel; Erbstein, Katarina; Reyes Hernández, Blanca Jazmín; Song, Changzheng; Tessi, Tomás; Petrasiunaite, Vesta; Färber, Naja; Distel, Kathrin; Maizel, Alexis (PLOS ONE, 2023)
Molecular cloning is a crucial technique in genetic engineering that enables the precise design of synthetic transcriptional units (TUs) and the manipulation of genomes. GreenGate and several other modular molecular cloning systems were developed about ten years ago and are widely used in plant research. All these systems define grammars for assembling transcriptional units from building blocks, cloned as Level 0 modules flanked by four-base pair overhangs and recognition sites for a particular Type IIs endonuclease. Modules are efficiently assembled into Level 1 TUs in a hierarchical assembly process, and Level 2 multigene constructs are assembled by stacking Level 1 TUs. GreenGate is highly popular but has three main limitations. First, using ad-hoc overhangs added by PCR and classical restriction/ligation prevents the efficient use of a one-pot, one-step reaction to generate entry clones and domesticate internal sites; second, a Level 1 TU is assembled from a maximum of six modules, which may be limiting for applications such as multiplex genome editing; third, the generation of Level 2 assemblies is sequential and inefficient. GreenGate 2.0 (GG2.0) expands GreenGate features. It introduces additional overhangs, allowing for the combination of up to 12 Level 0 modules in a Level 1 TU. It includes a Universal Entry Generator plasmid (pUEG) to streamline the generation of Level 0 modules. GG2.0 introduces GreenBraid, a convenient method for stacking transcriptional units iteratively for multigene assemblies. Importantly, GG2.0 is backwards compatible with most existing GreenGate modules. Additionally, GG2.0 includes Level 0 modules for multiplex expression of guide RNAs for CRISPR/Cas9 genome editing and pre-assembled Level 1 vectors for dexamethasone-inducible gene expression and ubiquitous expression of plasma membrane and nuclear fluorescent markers. GG2.0 streamlines and increases the versatility of assembling complex transcriptional units and their combination.